Call to arms great military speeches - Thompson, Julian (Quercus Publishing, 2009)
Call to Arms recounts more than 50 momentous and stirring speeches from a wide range of conflicts and eras. Complete with biographies of each military leader, the history of why each speech was significant and what happened in the battle as a result, this is a captivating history of the world at war.